Fenomena Hubungan Seksual Pada Wanita Premenopause Di Kota Makassar - Ramadani, Fitrah; Nurlinda, Andi; Haeruddin, Haeruddin (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Sexual dysfunction in women is an important reproductive health issue as it relates to the survival of a woman's reproductive function and has a major impact on the harmony of marital relationships. The purpose of this study was to determine the effectiveness of Belle Vie Transfer Factor on Sexual Dysfunction in Premenopausal Women in Makassar City. The research method is qualitative with phenomenology approach. Based on the research, there were 6 people who consisted of 4 people The results showed that the sexual dysfunction experienced by the informant did not make the mother to stop consuming TF belle vie because according to the informant although in the use of TF belle vie sometimes make the passion decrease did not dampen his desire to use TF belle vie consumption TF belle vie used informant is in accordance with their wishes -something. There are also informants who say that TF belle vie is good for use especially premenopausal women, but basically, all informants using TF belle vie receive well despite complaints such as sexual dysfunction. It is expected that the health officer in charge to improve the performance and attention in giving counseling especially about the use of TF belle vie